Teacher Wellbeing from the Perspective of Human Resource Management in Educational Institutions - Ilham Pebrian; Dudun Najmudin; Risan Sugiayasin; Yulan Tiarni Legistia (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
This study aims to describe the concept of teacher wellbeing from the perspective of educational human resource management, analyze the role of human resource management in improving teacher wellbeing, and identify human resource management factors that influence teacher wellbeing in educational institutions. This study employed a qualitative approach using library research methods. Data were collected through documentation techniques from reputable international journals, indexed national journals, academic books, and other scientific sources relevant to teacher wellbeing and educational human resource management. Data analysis was conducted using content analysis through the stages of data reduction, classification, interpretation, and conclusion drawing. The findings indicate that teacher wellbeing is influenced by several human resource management factors, including school leadership, organizational support, professional development, school work culture, and workload management. Supportive human resource management practices were found to enhance teachers’ work motivation, professional engagement, job satisfaction, and instructional quality. Conversely, human resource management practices that neglect teacher wellbeing may increase work stress and burnout among teachers. This study concludes that teacher wellbeing is an integral part of educational human resource management strategies in improving learning quality and educational outcomes sustainably.